A cluster based load balancing in long term evaluation self optimization network - Nandhini, R.; Udaya Nirmala Mary, R. (International Journal of Engineering and Technology, 2017)
Load Balancing (lb) is an important use case in long-term evaluation (lte) self-optimizing networks (sons). To overcome the potential ping-pong load transfer and low-convergence issues, we propose a clustering algorithm in lte sonÂ to solve the asymmetry traffic distribution among multiple cells .The proposed algorithm, which is referred to as clustering algorithm which optimally redistributes the load of cells to the multiple cells on clustering. Thus the clustered nodes formed selects the cluster head based upon the efficiency of the node. The cluster head is responsible for gathering the information about all the nodes within and outside the cluster, thus the speed gets increased and convergence time gets reduced by this method the hidden node problem gets avoided by implementing the enhanced protocol.